2020
DOI: 10.3390/w12123432
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Real-Time Control and Green Technologies to Urban Drainage Systems

Abstract: The increase in waterproof surfaces, a typical phenomenon of urbanization, on the one hand, reduces the volume of rainwater that naturally infiltrates the subsoil and, on the other, it determines the increase in speeds, flow rates, and outflow volume surface; at the same time, it causes a qualitative deterioration of the water. This study researched the optimal management of urban drainage systems via the combined application of real-time control and green technologies. A hydraulic model of the sewer system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In [34], a history of studies related to RTC at the same basin was presented, and the best performance obtained for reducing overflows was with the combined configuration of RTC + passive green roof. In [19], similar results were achieved when associating different configurations of real-time controlled sluice gates with scenarios containing green infrastructures in the system, such as the green roof, permeable pavement and stormwater harvesting reservoir. These combined effects of RTC application in drainage systems along with other mitigation techniques, such as NBS, are an important evolution of RTC applied to urban drainage; however, the benefits can be enhanced with actively real-time controlled NBS.…”
Section: Green Roofsupporting
confidence: 58%
See 2 more Smart Citations
“…In [34], a history of studies related to RTC at the same basin was presented, and the best performance obtained for reducing overflows was with the combined configuration of RTC + passive green roof. In [19], similar results were achieved when associating different configurations of real-time controlled sluice gates with scenarios containing green infrastructures in the system, such as the green roof, permeable pavement and stormwater harvesting reservoir. These combined effects of RTC application in drainage systems along with other mitigation techniques, such as NBS, are an important evolution of RTC applied to urban drainage; however, the benefits can be enhanced with actively real-time controlled NBS.…”
Section: Green Roofsupporting
confidence: 58%
“…Bioretention cells, as green roofs, also benefit from RTC aiming at water quality improvement for reuse. For green roofs, no specific studies of RTC were found, although there are studies that combine the RTC of the drainage system with passive green roof application scenarios that present good results for reducing peak flow and runoff volume in urban drainage [19,20]. As the RTC studies in NBS evolve, the application of multiple techniques to reach multiple scales of the urban drainage system can be a technological and sustainable alternative to increase urban resilience.…”
Section: Comparative Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable Urban Drainage Systems (Fryd et al 2010;Zhou 2014;Ellis & Lundy 2016;Lim & Lu 2016;Casal-Campos et al 2018;Arahuetes and Cantos 2019;Altobelli et al 2020;Kändler et al 2020;Lin et al 2020;Kwon et al 2020;Hager et al 2021), Low Impact Development and Best Management Practices (Strecker et al 2001;Dietz 2007;Motsinger et al 2016;Mani et al 2019;Nowogonśki 2020;Men et al 2020;Song et al 2020;Zhang et al 2020aZhang et al , 2020bKhurelbaatar et al 2021), Water Sensitive Urban Design (Lariyah et al 2011;Beecham & Razzaghmanesh 2015;Siekmann & Siekmann 2015;Marino et al 2018;Ahmed et al 2019) and Sponge City Programmes (Wang et al 2018) are some of the stormwater management schemes which are being adopted in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…There is a current lack of research on the strategy and implementation of local RTC (e.g. Carbone et al 2014;Garofalo et al 2016;Altobelli et al 2020), compared with studies of global control systems (e.g. Fuchs & Beeneken 2005;Dirckx et al 2011;Grum et al 2011;Seggelke et al 2013;Kroll et al 2018;Lund et al 2018;Meneses et al 2018).…”
Section: Introductionmentioning
confidence: 99%